Modification of Gemifloxacin Drug Antibacterial to Promising Anti-Prostate Cancer PC3 Azomethine Compounds: Synthesis and in Vitro Studies - Rand Thair Abdulkader; Reyam H. Marah; Aqeel Mohamed; Abbas K. Abbas (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
In this study, we report a novel azomethine derivatives synthesis (H and G) by reacting pure Gemifloxacin drugs with 2-aminobenzaldehyde and 2-methylbenzaldehyde. Spectroscopic techniques, such as FT‐IR spectroscopy, characterized the derivatives (G and H). All the synthesized derivatives (G and H) were evaluated in vitro against microorganisms such as Bacillus subtilis and E. coli by zone inhibition method and screened for antimicrobial activities and anti-Prostate cancer PC3 cell viability cell lines.